AN ANALYSIS OF MARKETING COMMUNICATION STRATEGIES IN BUILDING BRAND AWARENESS AT LA MORINGA KUPANG: English - Sinurat, Donal Anry Jaya (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study examines the marketing communication strategies employed by La Moringa Kupang, a local herbal brand in Indonesia, in its efforts to build brand awareness. The research adopts a qualitative approach using in-depth interviews, documentation analysis, and field observations. Findings reveal that La Moringa combines digital platforms particularly Instagram and WhatsApp with offline methods such as community engagement and word-of-mouth to communicate its brand values. The integration of educational content, local cultural narratives, and health-based messaging has significantly contributed to increased brand visibility and consumer trust. However, challenges such as limited digital reach and operational capacity hinder sustained brand performance. This study underscores the importance of aligning marketing communication with cultural context, audience behavior, and operational readiness. The results contribute to the growing literature on branding and local product marketing in emerging markets and suggest practical strategies for small businesses seeking to build brand equity through integrated communication. Keywords: brand awareness, marketing communication, digital strategy, La Moringa, local branding